2021
DOI: 10.1186/s12985-021-01592-2
|View full text |Cite
|
Sign up to set email alerts
|

ITRAQ-based quantitative proteomics reveals the proteome profiles of MDBK cells infected with bovine viral diarrhea virus

Abstract: Background Bovine viral diarrhea (BVD) which is caused by Bovine viral diarrhea virus (BVDV), is an acute, contagious disease. In spite of the use of vaccines and elimination projects, BVDV still causes severe economic losses to the cattle industry for the past few years. The current study presents a preliminary analysis of the pathogenic mechanisms from the perspective of protein expression levels in infected host cells at different points in time to elucidate the infection process associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…All of those changes enriched the lysosome pathway according to the KEGG database (Tables S10, S11 and S13). Other studies also indicated enrichment of the lysosome pathway after infection with the NADL (cp) strain [39]. The results of HCV studies indicated that there was no fusion of autophagosomes and lysosomes at an early stage of infection [40].…”
Section: Discussionmentioning
confidence: 98%
“…All of those changes enriched the lysosome pathway according to the KEGG database (Tables S10, S11 and S13). Other studies also indicated enrichment of the lysosome pathway after infection with the NADL (cp) strain [39]. The results of HCV studies indicated that there was no fusion of autophagosomes and lysosomes at an early stage of infection [40].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we collected the cell samples at 48 h post BVD infection for the integrated analysis of RNA-seq-based transcriptomics profiles and iTRAQ-based proteomics profiles of the BVDV-infected host cells. Although there has transcriptomic sequencing analysis for BVDV-infected host cells at 2 h, 6 h, 12 h, and 24 h post BVDV infection ( 21 ) and proteomic analysis for BVDV-infected host cells at 12 h, 24 h, and 48 h post BVDV infection ( 22 ), and a lot of DEGs and DEPs were obtained, just only one omics data type analysis is limited to correlation between mRNA and protein abundances in BVDV-infected host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using RNA-seq-based transcriptome analysis for PEDV-infected Vero cells, researchers observed that significant changes in the mTOR signaling pathway occurred at different time points after viral infection, and this was further experimentally confirmed to promote virus infection ( 20 ). Moreover, there have been several studies that report transcriptomic changes ( 21 ) and proteomic changes ( 22 ) in BVDV-infected host cells. However, only one omics data type analysis is limited to correlation between mRNA and protein abundances, such as transcriptomic data only represents the mRNA expression level, but not represents the presence of post-translational modifications, which was insufficient to predict protein expression levels from quantitative mRNA data.…”
Section: Introductionmentioning
confidence: 99%
“…iTRAQ is a high-throughput screening technology commonly used in quantitative proteomics [ 44 , 45 ]. iTRAQ technology has widely been used in the study of viral infection and disease development and for screening of biological markers [ 34 , 46 , 47 ]. To understand the role of PSS in ASFV replication, BMDMs were cultured with PSS and NPSS for 24 h, and DEPs in PSS and NPSS were identified using iTRAQ technology.…”
Section: Resultsmentioning
confidence: 99%